KARAKTERISTIK KOMITE AUDIT, KUALITAS LABA, DAN NILAI PERUSAHAAN - Abdullah, Syahriar (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2018)
Characteristics of the Audit Committee, Profit Quality and Company Value. This study analyzes the influence of audit committee characteristics on firm value. In addition, this study also examined the effect of moderating earnings quality on the relationship between audit committee characteristics and firm value. The sample research consisted of 164 companies listed on the Indonesia Stock Exchange in 2008 - 2009. The results of multiple linear regression analysis showed that the characteristics of the audit committee had a positive effect on the value of the company. Furthermore, the results of the analysis show that earnings quality moderates the relationship between audit committee size and meeting frequency with firm value. However, the results of the analysis have not been able to prove the moderating effect of earnings quality in the relationship between the independence and competence of the audit committee and the value of the company